Effect of Cutting Depth and Feed Speed to Surface Roughness in Lathe Process of Screw Conveyor Shaft (Case Study: PT. RAPP) - Junaidi Abdul Khair; Deni Pranata; Ujang Nuhadek (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
The metalworking process is one of the most important things in manufacturing of machine components, such as lathe process. Therefore, it is required continuously innovation to improve production quality. There are several ways to do this, for example by choosing the right type of tool, depth of cut, and spindle speed. In turning process for the production of goods is very important to produce a precision product in accordance to desiring of size and roughness. The turning speed of a lathe has a type of spindle rotation rate that is used according to production requirements, which uses a rotational speed that can be changed the rate of rotation of the machine, in order to determine the level of surface roughness in the turning process. One is affected the optimal conditions of the turning speed and feeding rate. In this paper, the variations of different rotational speed levels of low speed, medium speed and high speed according to variations of feeding rate in order to know the difference in roughness results for the screw conveyor shaft operation. The roughness was measured on the surface turning process using a reference of surface roughness stand comparator (ISO2632 / I-1975). The result of test revealed the greater speed of feed rate, the greater value of roughness. Reversely, the smaller speed of feed rate affected the lower roughness value.